2020
DOI: 10.3390/healthcare8020116
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Ankle–Foot Orthosis Using Wire on Static Balance of Patients with Stroke with Foot Drop: A Cross-Over Study

Abstract: The aim of this study was to investigate the immediate static balance effects of bare foot, UD-Flex ankle–foot orthosis (AFO), and AFO using wire (AOW) of patients with stroke with foot drop. Seventeen patients with stroke with foot drop (8 men and 9 women) were randomized to three conditions (bare foot, UD-Flex AFO, or AOW made with a flexible material). Static balance was assessed using the Zebris (Zebris GmbH, Isny, Germany) and BioRescue (RM Ingenierie, Rodez, France) pressure platform by a single examiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…In patients with stroke, ankle dorsiflexion is limitedand the alignment of the foot changes due to insufficient posterior glide of the talus, which increases the risk of abnormal ankle movement and ankle injury [21]. However, it has been reported that posterior talar glide in a weight-bearing position improved static balance by increasing afferent stimulation of the ankle joint in patients with stroke [22]. Application oftaping in the posterior-downward directionproduced a posterior talar glide and increased ankle dorsiflexion in patients with limited dorsiflexion [23] and thus improved static balance in patients with chronic stroke [8].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with stroke, ankle dorsiflexion is limitedand the alignment of the foot changes due to insufficient posterior glide of the talus, which increases the risk of abnormal ankle movement and ankle injury [21]. However, it has been reported that posterior talar glide in a weight-bearing position improved static balance by increasing afferent stimulation of the ankle joint in patients with stroke [22]. Application oftaping in the posterior-downward directionproduced a posterior talar glide and increased ankle dorsiflexion in patients with limited dorsiflexion [23] and thus improved static balance in patients with chronic stroke [8].…”
Section: Discussionmentioning
confidence: 99%
“…The Zebris platform for assessing the ground force reaction is a perfect tool for verifying the stability of the body in both static and dynamic tests [ 18 , 80 , 81 , 82 , 83 ]. Research on postural stability disorders using the Zebris platform is widely used in the clinical assessment of patients at risk of falling [ 84 , 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the assessment of postural stability, it is important to analyze parameters such as the length of the COP path, the path speed (VCOP), the area of the ellipse defined by the COP movements, and the symmetry of the limb loading [ 21 ]. Hence, many researchers analyze these parameters when assessing static balance [ 18 , 80 , 84 , 85 , 91 , 92 , 93 , 94 , 95 ]. The own research also confirmed a significant impact of exercise on the following balance parameters: 95% confidence ellipse area, COP path length, and VOP average velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle fatigue in plantarflexors is said to increase postural sway by interfering with the stability of the ankle joint [ 38 ]. In a previous study, in order to provide mechanical stability of the ankle after inducing muscle fatigue in the ankle of normal adults, the balance ability was increased by an intervention to control the inversion and eversion of the ankle [ 19 ], although this study was not applied to healthy adults with muscle fatigue at the ankle; in a previous study the use of AFO using a wire and dial, rather than the conventional plastic AFO, showed an improvement in the static balance measured using the BIORescue in stroke patients with foot drop [ 21 ]. The stability of the joint increased as the AFO wire on the medial and lateral sides of the ankle was controlled using the dial to adjust the position of the ankle joint, while covering the entire foot to press or fix the foot joint [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been used to improve the stability of the ankle, including stretching [ 17 ], exercise [ 18 ], taping [ 19 ], and joint mobilization [ 20 ]. A recent study investigated the effects of Ankle Foot Orthosis (AFO), wherein the ankle could be tightened using a wire and dial in patients with stroke, and showed that the patients using AFO who had wire and dial showed better improvement in balance control compared to the patients using the conventional AFO [ 21 ]. AFO is uncomfortable when worn due to its plastic material and large volume [ 22 ], and it rather decreases the dynamic balance [ 23 ].…”
Section: Introductionmentioning
confidence: 99%